Resilience To Negative Electronic Word Of Mouth: The Role Of Self-Congruity, Brand Attachment, And Prestige - Iha Haryani Hatta; Supriyadi Thalib; Harimurti Wulandjani; Amelia Oktrivina Siregar (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2022)
This study aims to: (1) introduce the concept of resilience to negative electronic word of mouth (eWOM); and (2) examine a process model from self-congruity, brand attachment, brand prestige, and resilience to negative eWOM using a moderation mediation model. A time-lag approach was conducted to collect data, involving 312 students from two universities in Jakarta. Moderation hierarchical regression using a macro process is used to test the hypothesis. The results show that resilience to negative eWOM can be strengthened through personal resources (self-congruity, brand attachment, and brand prestige). The brand attachment has been proven to be a vital factor that can strengthen resilience to negative eWOM, and this relationship becomes more robust as perceived brand prestige at a high level. These findings extend existing topics related to eWOM by presenting another form of consumer loyalty and trust in a brand through resilience to negative eWOM.